PROMOTING CHIARO HOTEL USING A WEBSITE - Ivana Kurniawati; Jusuf I Ibrahim (Kata Kita: Journal of Language, Literature, and Teaching, 2017)
Chiaro Hotel is a one-star hotel in Sidoarjo that is located at a strategic location. It is clean and comfortable family hotel. The problem of Chiaro Hotel is lack of promotion. Even though Chiaro Hotel has had some promotional tools, such as short promotional video, marketing booklet, and flyer, those promotional tools do not give good impact for the hotel because they do not show the uniqueness of Chiaro Hotel. Therefore, I make a website to solve Chiaro Hotel’s problem. This website can reach people in many places. Also, this website can help Chiaro Hotel to show the uniqueness that the hotel has. For my project, the website is mostly in English. The features in this website are “Home”, “About Us”, “Room”, “Facilities”, “Latest News”, ”Contact Us”, and “Booking Feature”. The benefits that Chiaro Hotel can get from this website are to be well-known among its competitors and get more customers.